THE IMPACT OF EMPOWERING LEADERSHIP BEHAVIOR ON ORGANIZATION-BASED SELF-ESTEEM: IS EMPLOYEES' SELF-EFFICACY PERCEPTION A MEDIATOR? (Third Sector Social Economic Review, 2023)
This study aims to determine the mediating effect of self-efficacy perceptions in the effect of empowering leadership behavior on employees' organization-based self-esteem. The research data were collected from 353 employees working in private jet charter companies operating throughout Turkey by face-to-face survey technique and the purposive sampling method was used. In the study, the scale developed by Konczak et al. (2000) for empowering leadership, the scale developed by Schwarzer and Jerusalem (1995) for self-efficacy, and the scale developed by Pierce et al. (1989) for organization-based self-esteem. Analyzes were tested with SPSS 25.0 and Process Macro 4.0 programs. In the study, it was used frequency analysis, factor, and reliability analysis, descriptive statistics, correlation analysis, and regression analysis. Regression analysis based on the bootstrap method was also used to determine the intermediary role, and Sobel test values were used to test the non-existence of the multicollinearity problem in the study. As a result of the research findings, it was found that empowering leadership positively affected organization-based self-esteem and self-efficacy perceptions. Self-efficacy perceptions also positively affected organization-based self-esteem. Additionally, self-efficacy perceptions were found to have a partial intermediary role in the effect of empowering leadership on organization-based self-esteem.
Keywords: Leadership; Empowering Leadership; Self-Efficacy; Organization-Based Self-Esteem; Mediator.